Business case - the state-of-the-art - Santos, J. P.; Pereira, L. (International Journal of Applied Decision Sciences, 2023)
Nowadays business case is a well-known and applied methodology in a multiple dimensionality of projects. This dimensionality of projects, where business case is being implemented, can range in the health sector, from gender equality to digital transformation due to its transversality. This paper intends to provide a comprehensive overview of the literature review of business case in terms of academic literature, searched keywords on the internet as well on the social network by providing a wide-ranging data analysis while providing a review in some of the research outcomes. Therefore, the present paper aims to provide a critically analysing occurrence and conjunction of the different data sources in a representative sample between 1977-2022, and to understand and integrate the current state of research on business cases in an attempt to provide a clear vision of the trends and future scenario of business case.